Factors Affecting to Consumer Behavior in Buying Finished Aluminum Lynn Through the Modern Trade Channel in Chiang Mai Area - ฟูไฟ อรรถพล; ใจคำ กมลทิพย์ (Ganesha Journal, 2018)
The objectives of this study were to 1) investigate consumer behavior in deciding to purchase finished aluminum Lynn products in Chiang Mai Province, 2) examine the factors affecting their behavior on their decision making to buy the products, and 3) explore the problems and solution guidelines of the consumers in deciding to purchase the products. The population consisted of 1,681,060 consumers in the province. The sample group involved in this study was composed of 400 customers buying the products through the modern trade channel at HomePro and Global House companies located in the province. The convenience sampling method was utilized to select the sample group and the questionnaires were used to collect the data. The descriptive statistics, Pearson Correlation and F-test were used to analyze the data. The study findings revealed that most of the sample group was males, accounting for 63.25%, and females, accounting for 36.75%, aged between 36 and 45 years. The majority of them were Bachelor degree holders with an average monthly income between 20,001 to 40,000 baht. The demographic factors relating to their behavior in purchasing the door/window Lynn aluminum products were age, education level, occupation and average monthly personal income, while gender was not related. The marketing mix factors relating to their behavior in buying the products included Product, Price, Place, Promotion, People, Process, and Physical Evidence respectively.